End-To-End Automation Maturity Models and Workforce Impact (International Journal of Scientific Research in Science and Technology, 2026)
The swift progress of the digital transformation speeded up the process of end-to-end automation implementation in industries that transformed the operations of the organization, decision-making, and workforce relationships. Automation maturity models have become valuable tools in evaluating and advising organizations to follow the steps of automation progressively, especially the fields of Industry 4.0, smart manufacturing, DevOps and hyperautomation. Although the current models of maturity offer systematic ways of integrating technology and processes, the implication of it on the workforce is still broken and in many cases immature. This paper discusses models of end-to-end automation maturity with a closer consideration on its influence over the workforce. The study examines the effects of the various degrees of automation maturity on the job description, skills needed, human-technology interface, and employee experience through reviewing existing automation, digital transformation, and Industry 4.0 maturity models. These results point to an increasing disconnect between technology and human-focused factors and the necessity to incorporate the aspect of workforce (including reskilling, ergonomics, organizational culture, and job satisfaction) into maturity measurements. The article would add to the literature by summarizing the perspectives on automation maturity and suggesting a more holistic perspective that would bring end-to-end automation advancement to sustainable workforce development.